You are invited to Log in or Register a free Frihost Account!

# Algebra Dividing

Pin3apple
I don't get it.
Anyone got a simple calculation way for a 15 year old?
TomS
1374 / 6 = ?

Start at the beginning:
Take the first number: 1/6 is smaller than one, so:
Take the first two numbers: 13. Think about how often 6 fits into 13. Right, two times. So now you write "2" and multiply with 6 and write the negativ result under the "13".
13 minus 12 is 1. Write 1 and the rest of the number (74) -> 174. Now you start all over.

 Code: 1374 / 6 = 2 -12 =174

1/7 is smaller than 1. so take 17. 6 fits two times into 17 again, so write 2 again, multyply with 6 and calculate 17-12 = 5 and write the rest of the number, which is 4. So you get 54

 Code: 1374 / 6 = 22 -12 =1...74 -> 174 17 -12 =5...4 -> 54

Now you have to look, hwo often 6 fits in to 54. The result is exactly 9. So the result if 1374 divided by 6 = 229

You can also check the last number by multiplying 6 and 9. It's 54. And 54 minus 54 = 0.
You're done.
BorisD
 Pin3apple wrote: I don't get it. Anyone got a simple calculation way for a 15 year old?

Can you elaborate please? division can range in difficulty greatly starting at simple 4/2 and on we go from there to matrices and diff equations, and so on. so what exactly do you have trouble grasping about division?

the bellow link maybe of use to you
http://www.aaamath.com/div.html
psleang
A 15 year old probably already know simple dvision like 132/3, and I don't think a 15 year old will learn matrices and diff equation. I am gussing it's somthing like xy^2z/yz^2?

y^2 is y squared and y^3 is y cubed. y^2 = y*y and y^3 = y*y*y,

so for example, what is y^3/y^2?
y^3/y^2 = y*y*y/y*y,
then you see 2 of the y in the denumerator cancels with 2 of the y in the numerator, so the answer is
y^3/y^2 = y^(3-2)=y (basically, just the exponent of y in the numerator minus exponent of y in denumerator)

Other examples,
y^5/y^2 = y^(5-2)=y^3
y^2/y^4 = y^(2-4)=y^(-2)

More complicated examples:
xy^2z/x^2yz = x^(1-2)y^(2-1)z^(1-1) = x^(-1)y^(1)z^(0)=y/x
Note: x = x^1, x^0 = 1 and x^(-1) = 1/x